Performance improvement of mediastinal lymph node severity detection using GAN and Inception network. (October 2020) - Tekchandani, Hitesh; Verma, Shrish; Londhe, Narendra
Highlights: Novel approach comprising of data augmentation and deep learning algorithms for improved and reliable malignancy detection of mediastinal lymph nodes (MLNs) in CT images. Comparison between various state-of-art GAN techniques like DCGAN, CGAN, ACGAN, Info GAN, and WGAN for application in data augmentation. Comparison between proposed Inception networks (Inception -v4 and Inception-ResNet-v2) and proven DenseNet network for severity detection of MLNs. Proposed approach achieved best evaluation parameters were, sensitivity = 93.65%, specificity = 96.67%, accuracy = 94.95%, AUC = 95% for severity detection of MLNs. Abstract: Background and objective: In lung cancer, the determination of mediastinal lymph node (MLN) status as benign or malignant influence treatment planning and survival rate. Invasive pathological tests for the classification of MLNs into benign and malignant have various shortcomings like painfulness, the risk associated with anesthesia, and depends to a large extent on skillset and preferences of the surgeon performing the test. Hence, computer-aided system for MLNs severity detection has been explored widely by the researchers. Very recently, in our earlier concluded work on non-invasive method for MLNs differential diagnosis in computed tomography (CT) images, combination of different data augmentation approaches and state-of-art fully convolutional network (FCN) were implemented to enhance the performance of malignancy detection. However, the performance of FCN network were highly depended on the selection of appropriate data augmentation approach and control of their hyperparameters. Moreover, a standard practice to get hierarchical features in convolutional neural network (CNN) models requires deeper stacking of layers. This leads to an increase in number of trainable parameters which prone to overfitting of the network. Methods: In view of the above mention limitations, in this paper, authors have proposed an approach that includes: 1) Generative Adversarial Network (GAN) for data augmentation, and 2) Inception network for malignancy detection. Unlike conventional data augmentation strategy, GAN based augmentation approach generates data that correlates to original data distribution. In the case of Inception based model, it uses multiple size kernels with factorized convolution for hierarchical feature extraction. This helps to a significant reduction in trainable parameters and the problem of overfitting. Results: In this paper, experiments with different GAN approaches, as well as with different Inception architectures, are conducted to evaluate and justify the selection of appropriate GAN and Inception architecture, respectively for MLNs severity detection. The proposed approach achieves superior results with an average accuracy, sensitivity, specificity, and area under curve of 94.95%, 93.65%, 96.67%, and 95%, respectively. Conclusion: The obtained results validate the usefulness of GANs for data augmentation in the differential diagnosis of benign and malignant MLNs. The proposed Inception network based classifier for malignancy detection shows promising results compared to all investigated methods presented in various literature.